Nanostructure Formation in the Nickel-Chrome Coating After Duplex Treatment - N.V. Prohorenkova; A.D. Pogrebnjak; D.L. Alontseva; M.V. Kaverin (Журнал нано- та електронної фізики)
New results of research of the structure and phase state and mechanical properties of the coatings made of industrial composite powders based on Ni-Cr are presented and analyzed. Coatings were deposited by the plasma detonation method on the stainless steel substrate, and then they were exposed to the electron irradiation or the plasma-jet melting. TEM metallography, scanning electron microscopy, X-ray photoelectron spectroscopy, X-ray spectral analysis, X-ray structural phase analysis, determination of the microhardness and the corrosion resistance are chosen as the main research methods. It is established experimentally that before irradiation PG-19N-01 coating consists of the nanocrystalline γ-phase based on Ni and the microcrystalline CrNi3 phase. Regions of nanograins with various crystallographic lattice orientations are found in the nanocrystalline phase. The nanograin and microcrystallite sizes, the type and parameters of their lattices are defined. Deposition of the powder PG-10N-01, PG-19N-01 and PGAN-33 coatings by the plasma detonation method with the subsequent surface melting leads to the formation of multiphase dense coatings with the inter-metallic strengthening compounds, oxides and carbides. The irradiated coatings possess high microhardness, which is about 5 GPа, and corrosion resistance in sea-water.